a) Ta có: O(0; 0; 0)
Vì OABC.O’A’B’C’ là hình hộp nên AOBC là hình bình hành. Do đó:\(\overrightarrow {OA} = \overrightarrow {CB} \Rightarrow \left\{ \begin{array}{l}{x_A} = {x_B} - {x_C}\\{y_A} = {y_B} - {y_C}\\{z_A} = {z_B} - {z_C}\end{array} \right. \Rightarrow \left\{ \begin{array}{l}{x_C} = {x_A} - {x_B} = 1\\{y_C} = {y_A} - {y_B} = - 2\\{z_C} = {z_A} - {z_B} = - 1\end{array} \right. \Rightarrow C\left( {1; - 2; - 1} \right)\)
b) Vì OABC.O’A’B’C’ là hình hộp nên
\(\overrightarrow {OO'} = \overrightarrow {CC'} \Rightarrow \left\{ \begin{array}{l}{x_{O'}} = {x_{C'}} - {x_C} = 1\\{y_{O'}} = {y_{C'}} - {y_C} = - 1\\{z_{O'}} = {z_{C'}} - {z_C} = 7\end{array} \right. \Rightarrow O'\left( {1; - 1;7} \right)\)
\(\overrightarrow {AA'} = \overrightarrow {CC'} \Rightarrow \left\{ \begin{array}{l}{x_{A'}} - {x_A} = {x_{C'}} - {x_C} = 1\\{y_{A'}} - {y_A} = {y_{C'}} - {y_C} = - 1\\{z_{A'}} - {z_A} = {z_{C'}} - {z_C} = 7\end{array} \right. \Rightarrow \left\{ \begin{array}{l}{x_{A'}} = 2\\{y_{A'}} = 0\\{z_{A'}} = 6\end{array} \right. \Rightarrow A'\left( {2;0;6} \right)\)
\(\overrightarrow {BB'} = \overrightarrow {CC'} \Rightarrow \left\{ \begin{array}{l}{x_{B'}} - {x_B} = \left( {{x_{C'}} - {x_C}} \right) = 1\\{y_{B'}} - {y_B} = \left( {{y_{C'}} - {y_C}} \right) = - 1\\{z_{B'}} - {z_B} = \left( {{z_{C'}} - {z_C}} \right) = 7\end{array} \right. \Rightarrow \left\{ \begin{array}{l}{x_{B'}} = 1\\{y_{B'}} = 2\\{z_{B'}} = 7\end{array} \right. \Rightarrow B'\left( {1;2;7} \right)\)